Metabolic profile and psychological variables after bariatric surgery: association with weight outcomes - Brandao, Isabel (2015)
Purpose This study aims to examine associations between metabolic profile and psychological variables in post-bariatric patients and to investigate if metabolic and psychological variables, namely high-density lipoprotein cholesterol (HDL-C), triglycerides (TG), glycated hemoglobin (HbA 1c), impulsivity, psychological distress, depressive and eating disorder symptoms are independently associated with percentage of excess weight loss (%EWL) after bariatric surgery.Methods One hundred and fifty bariatric patients (BMI = 33.04 +/- 5.8 kg/m(2)) who underwent to bariatric surgery for more than 28.63 +/- 4.9 months were assessed through a clinical interview, a set of self-report measures and venous blood samples. Pearson's correlations were used to assess correlations between %EWL, metabolic and psychological variables. Multiple linear regression was conducted to investigate which metabolic and psychological variables were independently associated with %EWL, while controlling for type of surgery.Results Higher TG blood levels were associated with higher disordered eating, psychological distress and depression scores. HDL-C was associated with higher depression scores. Both metabolic and psychological variables were associated with %EWL. Regression analyses showed that, controlling for type of surgery, higher % EWL is significantly and independently associated with less disordered eating symptoms and lower TG and HbA_1c blood concentrations (R-2 aj = 0.383, F (4, 82) = 14.34, p < 0.000).Conclusion An association between metabolic and psychological variables, particularly concerning TG blood levels, disordered eating and psychological distress/depression was found. Only higher levels of disordered eating, TG and HbA_1c showed and independent correlation with less weight loss. Targeting maladaptive eating behaviors may be a reasonable strategy to avoid weight regain and optimize health status post-operatively.